2011
DOI: 10.2527/jas.2010-3348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abomasal oligofructose on blood and feces of Holstein steers

Abstract: Subacute ruminal acidosis can result in increased flow of fermentable substrates to the hindgut, which can negatively affect animal health and productivity. However, animal responses to increased hindgut fermentation independent of subacute ruminal acidosis have rarely been evaluated. This study determined the impact of abomasal dosage of a fermentable carbohydrate on animal performance and blood and fecal variables. Six ruminally cannulated Holstein steers fed a lactating dairy cow ration were used in a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
2
14
2
Order By: Relevance
“…In this study the APP response possibly resulted from ruminitis due to acidosis, translocation of pro-inflammatory molecules from the rumen across damaged epithelium or a systemic acidosis due to an accumulation of organic acids in the circulation. However another study on the effect of oligofructose in the diet has reported that no effect was found in Hp or SAA concentrations [201] the difference from the previous report possibly being that in the latter study the treatment did not produce metabolic acidosis.…”
Section: 3mentioning
confidence: 72%
“…In this study the APP response possibly resulted from ruminitis due to acidosis, translocation of pro-inflammatory molecules from the rumen across damaged epithelium or a systemic acidosis due to an accumulation of organic acids in the circulation. However another study on the effect of oligofructose in the diet has reported that no effect was found in Hp or SAA concentrations [201] the difference from the previous report possibly being that in the latter study the treatment did not produce metabolic acidosis.…”
Section: 3mentioning
confidence: 72%
“…Rumen and faecal content of VFA and lactic acid were evaluated by high‐performance liquid chromatography following the procedures of Muck and Dickerson () as described by Mainardi, Hengst, Nebzydoski, Nemec, and Gressley (). The endotoxin concentration of faecal samples was determined using a commercial chromogenic endpoint amebocyte lysate kit according to manufacturer instructions (Pierce LAL Chromogenic Endotoxin Quantification Kit, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…However, the single pulse dose nature of that model caused more dramatic changes in fecal composition than typically observed with SARA (Mainardi et al, 2011). Additionally, although oligofructose infusion delivered a precise amount of fructans to intestinal microbes, starch is the substrate primarily responsible for the hindgut effects of SARA (Hall, 2002;Li et al, 2012).…”
Section: Effect Of Abomasal Carbohydratesmentioning
confidence: 99%
“…Fecal SCFA were determined as described by Mainardi et al (2011). Briefly, 25 ± 0.5 g of feces were acidified, stored at -20°C, and analyzed using HPLC using procedures described by Muck and Dickerson (1988).…”
Section: Fecal Sampling and Analysesmentioning
confidence: 99%
See 1 more Smart Citation